Biodegradation of oil-contaminated soils by Aspergillus Niger and Aspergillus Flavus (Acta Scientiarum. Animal Sciences, 2026)
The use of microorganisms is one of the most important methods widely used in the world to treat hydrocarbon pollution by decomposing them. A nutrient medium with mineral salts and added crude oil was used to grow fungi isolated from contaminated sites, namely Aspergillus flavus and Aspergillus niger. During the incubation period of 20 and 40 days, gas chromatography (TPH) was used to measure hydrocarbons. Over a similar period of time, the results revealed that Aspergillus flavus performed less well in decomposition (32.5% and 60.2%) against Aspergillus niger, which recorded higher decomposition rates (44.5% and 74.6%). This leads to the fact that fungi, through their enzymes, are able to analyze fungal pollutants in the soil.